Evaluation of a full-scale wastewater treatment plant upgraded with ozonation and biological post-treatments: Abatement of micropollutants, formation of transformation products and oxidation by-products. (1st February 2018) - Bourgin, Marc; Beck, Birgit; Boehler, Marc; Borowska, Ewa; Fleiner, Julian; Salhi, Elisabeth; Teichler, Rebekka; von Gunten, Urs; Siegrist, Hansruedi; McArdell, Christa S.
Abstract: To protect the ecosystem and drinking water resources in Switzerland and in the countries of the downstream catchments, a new Swiss water protection act entered into force in 2016 aiming to reduce the discharge of micropollutants from wastewater treatment plants (WWTPs). As a consequence, selected WWTPs must be upgraded by an advanced treatment for micropollutant abatement with suitable and economic options such as (powdered) activated carbon treatment or ozonation. WWTP Neugut (105′000 people equivalent) was the first WWTP in Switzerland to implement a long-term full-scale ozonation. Differing specific ozone doses in the range of 0.35–0.97 g O3 /g DOC were applied to determine the adequate ozone dose to fulfill the requirements of the Swiss water protection act. Based on this assessment, a specific ozone dose of 0.55 g O3 /g DOC is recommended at this plant to ensure an average abatement of the twelve selected indicator substances by ≥80% over the whole treatment. A monitoring of 550 substances confirmed that this dose was very efficient to abate a broad range of micropollutants by >79% on average. After ozonation, an additional biological post-treatment is required to eliminate possible negative ecotoxicological effects generated during ozonation caused by biodegradable ozonation transformation products (OTPs) and oxidation by-products (OBPs). Three biological treatments (sand filtration, moving bed, fixed bed) and granular activated carbon (GAC, fresh and pre-loaded) filtration were evaluated as post-treatments after ozonation. In parallel, a fresh GAC filter directly connected to the effluent of the secondary clarifier was assessed. Among the three purely biological post-treatments, the sand filtration performed best in terms of removal of dissolved organic carbon (DOC), assimilable organic carbon (AOC) and total suspended solids (TSS). The fresh activated carbon filtration ensured a significant additional micropollutants abatement after ozonation due to sorption. The relative abatement of the indicator substances ranged between 20 and 89% after 27′000 bed volumes (BV) and was still substantial at 50′000 BV. In an identical GAC filter running in parallel and being fed with the effluent of the secondary clarifier, the elimination was less efficient. Seven primary OTPs (chlorothiazide and six N -oxides) formed during ozonation could be quantified thanks to available reference standards. Their concentration decreased with increasing specific ozone doses with the concomitant formation of other OTPs. The seven OTPs were found to be stable compounds and were not abated in the biological post-treatments. They were sorbed in the fresh GAC filter, but less efficiently than the corresponding parent compounds. Two OBPs, bromate (BrO3 − ) and N -nitrosodimethylamine (NDMA), were formed during ozonation but did not exceeded 5 μg/L for bromate and 30 ng/L for NDMA at the recommended specific ozone dose of 0.55 g O3 /g DOC. NDMA was well abated in all post-treatments (minimum 41% during fixed bed filtration, maximum 83% during fresh GAC filtration), while bromate was very stable as expected. Graphical abstract: Highlights: The abatement of around 200 micropollutants during biological treatment and ozonation. Micropollutants removal during GAC filtration before and after ozonation was compared. The fate of 19 ozonation products was investigated in various post-treatments. Bromate and NDMA levels in the receiving surface water were below critical values.